Karakteristik Bakteri Probiotik dari Saluran Pencernaan Ayam Kampung sebagai Kandidat Pakan Ayam - Jabir, Nurmumin; Oktavia, Rizka (Al-Kimia, 2022)
Probiotics are living organisms that can provide a beneficial effect on the host's health when consumed in sufficient quantities by improving the balance of the intestinal microflora when it enters the digestive tract. Probiotics can be bacteria, fungi, or yeast, but the most probiotics are bacteria. Microbes in probiotic products function to improve health and are classified as healthy and functional foods. This study aimed to isolate, characterize and identify probiotic bacteria in the digestive tract of native chickens as bacteria that degrade organic compounds. Characterization of probiotic bacteria included observation of colony morphology, gram staining, bacterial degradation test for cellulose, pectin, and starch, calculating dissolution index, and making probiotic animal feed. The results showed that 15 bacterial isolates were obtained, two of which were determined as candidates for chicken feed. The two isolates showed probiotic characteristics.